2013
DOI: 10.1089/aid.2012.0309
|View full text |Cite
|
Sign up to set email alerts
|

Persistently Elevated Serum Interleukin-6 Predicts Mortality Among Adults Receiving Combination Antiretroviral Therapy in Botswana: Results from a Clinical Trial

Abstract: Elevated serum levels of inflammatory biomarkers have been associated with increased mortality and morbidity among HIV-infected individuals receiving combination antiretroviral therapy (cART) in European and U.S. cohorts. Few similar data are available from sub-Saharan Africa, where most cART-treated adults reside and the prevalence of advanced immunosuppression and opportunistic infections (OIs) at cART initiation is higher. This was a retrospective nested case-control analysis of clinical trial data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…53,54 As obesity prevalence among people living with HIV rises, 17 further investigation into the long-term implications of this weight gain is needed. Future prospective studies should assess whether intentional weight loss or similar interventions affect inflammatory processes similarly in HIV infected and uninfected people.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 As obesity prevalence among people living with HIV rises, 17 further investigation into the long-term implications of this weight gain is needed. Future prospective studies should assess whether intentional weight loss or similar interventions affect inflammatory processes similarly in HIV infected and uninfected people.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple biomarker studies have identified a higher IL-6 level as a predictor of subsequent mortality 9,22,23 . A number of explanations could account for the lack of association between IL-6 levels and death found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-6 production is associated with severe pathogenicity in HIV infection in humans and SIV infection in RM (38)(39)(40)(41). For example, SIVsmmPBj8 infection of RM results in death within a few weeks and induces significant IL-6 production, which may be a cause or effect of the pathogenic course of infection (42).…”
Section: Figmentioning
confidence: 99%